Linking men's voice pitch to actual and perceived trustworthiness across domains. (12th October 2019) - Schild, Christoph; Stern, Julia; Zettler, Ingo
Abstract: Previous research suggests that judgments about a male speaker's trustworthiness vary due to the speaker's voice pitch (mean F 0) and differ across domains. However, mixed results in terms of the direction and extent of such effects have been reported. Moreover, no study so far has investigated whether men's mean F 0 is, indeed, a valid cue to their self-reported and behavioral trustworthiness, and whether trustworthiness judgments are accurate. We tested the relation between mean F 0 and actual general, economic, and mating-related trustworthiness in 181 men, as well as trustworthiness judgments of 95 perceivers across all three domains. Analyses show that men's mean F 0 is not related to Honesty–Humility (as a trait indicator of general trustworthiness), trustworthy intentions, or trust game behavior, suggesting no relation of mean F 0 to general or economic trustworthiness. In contrast, results suggest that mean F 0 might be related to mating-related trustworthiness (as indicated by self-reported relationship infidelity). However, lower mean F 0 was judged as more trustworthy in economic but less trustworthy in mating-related domains and rather weakly related to judgments of general trustworthiness. Trustworthiness judgments were not accurate for general or economic trustworthiness, but exploratory analyses suggest that women might be able to accurately judge men's relationship infidelity based on their voice pitch. Next to these analyses, we report exploratory analyses involving and controlling for additional voice parameters. Lay Summary: Voice pitch does not seem to be a valid indicator of a male speaker's general or economic trustworthiness. In contrast, a male's voice pitch allows accurate judgments about his self-reported past infidelity. In our study, men with deeper voices were more likely to report having cheated in a committed relationship. Additionally, female raters were able to judge relationship infidelity accurately from short voice recordings.